Exosomally Targeting microRNA23a Ameliorates Microvascular Endothelial Barrier Dysfunction Following Rickettsial Infection - Zhou, Changcheng; Bei, Jiani; Qiu, Yuan; Chang, Qing; Nyong, Emmanuel; Vasilakis, Nikos; Yang, Jun; Krishnan, Balaji; Khanipov, Kamil; Jin, Yang; Fang, Xiang; Gaitas, Angelo; et al. (Frontiers in Immunology, 2022)
Spotted fever group rickettsioses caused by Rickettsia (R) are devastating human infections, which mainly target microvascular endothelial cells (ECs) and can induce lethal EC barrier dysfunction in the brain and lungs. Our previous evidence reveals that exosomes (Exos) derived from rickettsial-infected ECs, namely R-ECExos, can induce disruption of the tight junctional (TJ) protein ZO-1 and barrier dysfunction of human normal recipient brain microvascular endothelial cells (BMECs). However, the underlying mechanism remains elusive. Given that we have observed that microRNA23a (miR23a), a negative regulator of endothelial ZO-1 mRNA, is selectively sorted into R-ECExos, the aim of the present study was to characterize the potential functional role of exosomal miR23a delivered by R-ECExos in normal recipient BMECs. We demonstrated that EC-derived Exos (ECExos) have the capacity to deliver oligonucleotide RNAs to normal recipient BMECs in an RNase-abundant environment. miR23a in ECExos impairs normal recipient BMEC barrier function, directly targeting TJ protein ZO-1 mRNAs. In separate studies using a traditional in vitro model and a novel single living-cell biomechanical assay, our group demonstrated that miR23a anti-sense oligonucleotide-enriched ECExos ameliorate R-ECExo-provoked recipient BMEC dysfunction in association with stabilization of ZO-1 in a dose-dependent manner. These results suggest that Exo-based therapy could potentially prove to be a promising strategy to improve vascular barrier function during bacterial infection and concomitant inflammation.